The present time as a challenge to historiography and history teaching in the context of a democratic crisis (Tempo e Argumento, 2023)
The article analyzes effects of the Brazilian democratic crisis of the present time in historiography and in the teaching of history in Brazil. Starting from the hypothesis that the crisis is an expression of an ambivalence between movements of corrosion and widening of the concept of democracy, forged in terms of the process of redemocratization synthesized in the 1988 Constitution, it suggests that the contemporary environment in crisis reshapes the ways of narrating history by its specialists - historians and teachers - highlighting the need to widen disciplinary boundaries according to the demands of the present time. It examines the negationist discursive tactics - associated with the political project of democratic corrosion - and the movements for the widening of democratization, destabilizing class-race-gender structures, founders of exclusions and hierarchies of differences in Brazilian social formation.
Keywords: history of the present time; democratic crisis; historiography and history teaching